Human ATP-binding cassette transporter 1 (ABC1): Genomic organization and identification of the genetic defect in the original Tangier disease kindred - Remaley, Alan T. (The National Academy of Sciences, 1999)
Tangier disease is characterized by low serum high density lipoproteins and a biochemical defect in the cellular efflux of lipids to high density lipoproteins. ABC1, a member of the ATP-binding cassette family, recently has been identified as the defective gene in Tangier disease. We report here the organization of the human ABC1 gene and the identification of a mutation in the ABC1 gene from the original Tangier disease kindred. The organization of the human ABC1 gene is similar to that of the mouse ABC1 gene and other related ABC genes. The ABC1 gene contains 49 exons that range in size from 33 to 249 bp and is over 70 kb in length. Sequence analysis of the ABC1 gene revealed that the proband for Tangier disease was homozygous for a deletion of nucleotides 3283 and 3284 (TC) in exon 22. The deletion results in a frameshift mutation and a premature stop codon starting at nucleotide 3375. The product is predicted to encode a nonfunctional protein of 1,084 aa, which is approximately half the size of the full-length ABC1 protein. The loss of a Mnl1 restriction site, which results from the deletion, was used to establish the genotype of the rest of the kindred. In summary, we report on the genomic organization of the human ABC1 gene and identify a frameshift mutation in the ABC1 gene of the index case of Tangier disease. These results will be useful in the future characterization of the structure and function of the ABC1 gene and the analysis of additional ABC1 mutations in patients with Tangier disease.